The Effect of Tibolon on Bone Mineral Density and Calcium Metabolism in Postmenopausal Women - Ahmet C. Çalışkan; H. Levent Keskin; Alptekin Alagöz; Ertan Akpınar; Sami Gürbüz; Serdar Oğuz (Galenos Yayinevi, 2003)
Objective: To investigate the effects of tibolone on bone mineral density and serum and urinary calcium metabolism in postmenopausal women. Material and Methods: This randomized, placebo controlled study was conducted in Dr. Zekai Tahir Burak Women's Health Education and Research Hospital in the Menopause Department on 241 postmenopausal women between 1999 and 2000. 30 women were excluded from the study because of the adverse effects (n=16) and loss to follow-up (n=14). Totally 211 patients results were evaluated; 109 in the treatment group (tibolone +calcium) and 102 in control group The control group received only calcium (1000 mg/day). The bone mineral density of L1-4 lumbar vertebra and femur neck were calculated by Dual Energy X-ray Absorbsiometry (DEXA) at first visit and 12th and 24th months. At the same time serum and urinary calcium metabolism products were also calculated. Results: Bone mineral density showed significant increase in tibolone group while a decrease was detected in the control group (p<0.01). The increase in femur neck density was greater than lumbar vertebra at the end of 12th month (p<0.05). At the end of second year urinary calcium/ creatinin ratio was reduced significantly in tibolone group (p<0.05). Vaginal bleeding was 27% in tibolone group, 15% in control group and this result was not statistically significant (p>0.05). Conclusion: Tibolone is an effective, well-tolerable treatment option which is effective in women for the prevention of osteoporosis in postmenoposal period.